The effect of regional entrepreneurship culture on economic development: Evidence for Germany - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We use the historical self-employment rate as an indicator of a regional culture of entrepreneurship and link this measure to economic growth in recent periods. The results indicate that German regions with a high level of entrepreneurship in the mid- 1920s have higher start-up rates about 80 years later. Furthermore, we find that the effect of current start-up activity on regional employment is significantly higher in regions with a pronounced entrepreneurial culture. We conclude that a regional culture of entrepreneurship is an important resource for regional growth.
Keywords: L26; R11; O11; 330; economic development; entrepreneurship; entrepreneurship culture; institutions; new business formation; self-employment